Neutrophil–lymphocyte ratio and subclinical atherosclerosis in essential hypertensive patients - Petramala, Luigi; Circosta, Francesco; Cremonesi, Leonardo; Menichelli, Danilo; Cimò, Antonino; Servello, Adriana; Anastasi, Emanuela; Marino, Luca; Letizia, Claudio (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesArterial hypertension plays a significant role in promoting organ damage and the development of atherosclerosis. The neutrophil–lymphocyte ratio (NLR) is an accessible and cost-effective biomarker that has been strongly associated with adverse outcomes in patients with coronary artery disease and chronic heart failure. The aim of this study was to evaluate the clinical utility of NLR as a surrogate biomarker of subclinical atherosclerotic damage in patients with essential hypertension.MethodsFrom January 2024 to November 2024, we consecutively enrolled 346 patients with essential hypertension. For all patients, we collected medical history, anthropometric data, biochemical analyses, and subclinical organ damage, including 24-h urinary excretion of microalbuminuria, carotid intima–media thickness, and transthoracic echocardiography. We excluded patients with arterial hypertension, coronary artery disease, or cerebrovascular or peripheral artery disease.ResultsIn our study, we found that patients with higher NLR were associated with high blood pressure values, the use of more than three antihypertensive medications, and a higher prevalence of dyslipidemia and obstructive sleep apnea syndrome. Moreover, elevated NLR values correlated with a higher prevalence of subclinical organ damage (left cardiac ventricular mass, carotid atherosclerosis, and increased microalbuminuria).ConclusionsOur study shows that in patients with essential hypertension, NLR is significantly correlated with some cardiovascular comorbidities and subclinical organ damage.